CREATING A SPACE FOR INNOVATIVE TEACHING, LEARNING AND SERVICE DELIVERY: The Story of the Dalhousie University School of Social Work Community Clinic - Karabanow, Jeff; Hall, Cyndi; Davies, Harriet; Murphy, Andrea; Martin-Calero, Piedad; Oulton, Sarah; Titus, Michelle (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2018)
The School of Social Work Community Clinic opened its doors in June, 2014 in a donated space in a local parish hall. With very few resources initially the clinic now has its own rented space, serves a caseload of over 200 marginalized community members and has provided field placement experiences for over 75 BSW/MSW, pharmacy, psychology, nutrition, nursing, and occupational therapy students. In this article, we will highlight the steps we took to create and develop the Clinic with a social justice/anti-oppressive foundation, and the practice-teaching approaches we use with our students. We will also describe how we are integrating an interprofessional and community-university partnership culture in our day-to-day work with marginalized populations. This process will be described and discussed in relation to both interprofessional health education and the provision of relevant and meaningful services to clients. The community development techniques we used to develop our clinic and how we have been able to grow and expand will be highlighted. The partners we have established in government, the university, and the community that have contributed to a more sustainable future are also described.